2017
DOI: 10.1007/s11666-017-0592-z
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Finite Element Simulations of Thermal Barrier Coatings

Abstract: To understand the stress evolution and failure mechanisms of thermal barrier coatings (TBCs), finite element simulations are an invaluable tool. Simulations are especially useful to unwrap complex interactions of different phenomena at high temperature, including creep, sintering, diffusion, and oxidation. However, the correct setup and evaluation of a finite element model for this problem are difficult. This article reviews critical issues in modelling TBC systems. Some of the most important aspects are as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…A detailed review on various modelling methodologies and failure mechanisms in TBC systems addressed through computational modelling can be found in [20]. A second review on the influence of modelling choices in terms of interface morphology, boundary conditions, dimensionality and material models on the TBC response is presented in [21]. They provided guidelines and strategies for effectively modelling the stress evolution and the crack propagation in TBC systems.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review on various modelling methodologies and failure mechanisms in TBC systems addressed through computational modelling can be found in [20]. A second review on the influence of modelling choices in terms of interface morphology, boundary conditions, dimensionality and material models on the TBC response is presented in [21]. They provided guidelines and strategies for effectively modelling the stress evolution and the crack propagation in TBC systems.…”
Section: Introductionmentioning
confidence: 99%
“…Because the TBC sample is a three-dimensional (3D) structure, the σ t in the coating analyzed by the 2D model may be different from that in the real coating. Bäker and Seiler [134] used two kinds of 3D models to study σ t in the ceramic layer during a cooling process, as shown in Fig. 25.…”
Section: Thermal Mismatch Stressmentioning
confidence: 99%
“…For more accurate results, the FE model must incorporate the bond strength for the coating and substrate while including plasticity (with stresses for various plastic strain values) in the model and to use cohesive behaviour between the coating and the substrate to study the delamination strength. It has also been demonstrated that it is not straightforward to estimate the behaviour of cracks from a micromechanical stress simulation [37] because the formation and propagation of microcracks changes the stress state significantly. Importantly, if the interest is more in understanding the main features of stress evolution during compression loading than in performing quantitatively accurate calculations, a simple finite element simulation is advantageous.…”
Section: Finite Element Analysis Of Diametral Compression Loadingmentioning
confidence: 99%
“…may not be straight forward in modelling. Although a more realistic simulations [e.g [37][38][39][40][41][42]. (beyond the scope of current work) can yield valuable insights into the effect of the microstructure on stresses or crack propagation.…”
mentioning
confidence: 99%